FAKTOR HUMAN, ORGANIZATION, DAN TECHNOLOGY DALAM PENGGUNAAN APLIKASI S IMPUS UNTUK PENDAFTARAN PASIEN DI PUSKESMAS MULYOREJO SURABAYA - Nadia Rizqi Aulia (Universitas Airlangga, 2017)
The used of application SIMPUS at Puskesmas Mulyorejo Surabaya for patient registration has not been optimal. It is necessary to identify related factors to make the patient registration service work well with SIMPUS application support. This research describes the variable of human factor, organization, and technology to describe the factors related to S IMPUS application at P uskesmas Mulyorejo Surabaya. The research approach used is quantitative descriptive with data collection method of questionnaire, observation, documentation and in-depth interview. Research respondents cover all officers who have used and operated S IMPUS. The results explain that S IMPUS application has not been used steadily because of frequent damage so that p atient registration is also done manually. The human factor condition that determines the proper use of S IMPUS applications is the experience and reception of the officers of the SIMPUS application. Conversely, the less good is the knowledge and satisfaction of the officers. The condition factors of the organization that determine the proper use of S IMPUS applications are the ease of adopting technology, the habit of sharing information, the liveliness of proposing improvement, teamwork, top management feedback, and the availability of SOP. Organizational factors that have not worked well are data re-checking and lack of regular evaluation. Condition of technological factors that have been running well among other applications easy to use, studied, flexible, accurate, and available at any time needed. Technological factors that have not been running well is the speed of the system, completeness of information, application quality assurance, repair response speed, and follow-up handling disorders. The study recommends the need for training and technical guidance, system development to change the service that is still manual, data re-checking, SIMPUS quality improvement to avoid errors, the speed of damage handling response, and regular evaluation on an ongoing basis.